Normalized Difference Vegetation Index Serves as a Vegetation Indicator for Hydrometeorological Disaster Risk Mitigation in Post-Mining Reclamation Land - Dewi Nur Indah Sari; Henyningtyas Suhel; Arif Eko Wibawanto (LPPM Universitas Andalas, 2026)
Mining activities in South Kalimantan have had a significant impact on the environment, particularly related to the risk of hydrometeorological disasters such as floods and landslides. Post-mining land reclamation is a crucial effort in mitigating these risks. Sustainable reclamation is key to risk mitigation and can be monitored through the Normalized Difference Vegetation Index (NDVI) as an indicator of vegetation density and health. High NDVI values indicate successful reclamation. The primary objective of this research is to evaluate the effectiveness of post-mining reclamation as a hydrometeorological disaster mitigation strategy by assessing vegetation density and health. The study utilizes Sentinel-2 Level-2A satellite imagery processed on the Google Earth Engine (GEE) platform to calculate the NDVI. To ensure data reliability, the results were validated through field measurements using the purposive sampling method and canopy cover estimation to achieve a high level of accuracy. The results show an accuracy rate of 90%, with dense vegetation dominating and an index value of 0.6–0.9, indicating that reclamation has successfully increased vegetation cover and plays a significant role in mitigating floods and landslides.